Effect of Exposure Time of Triiodothyronine (T3) Hormone Solution on Development, Growth and Survival Rate of Giant Gouramy (Osphronemus gouramy Lac.) - M. Sakdiah; M. Zairin Junior; O. Carman (Jurnal Akuakultur Indonesia)
ABSTRACT